Masjid Besar Kauman Semarang : Sebuah Kajian Gaya Arsitektur dan Ornamen - Achmad Sidiq (Balai Penelitian dan Pengembangan Agama Semarang, 2011)
Masjid Besar Kauman Semarang which is simply called as Masjid Besar Kauman is an ancient mosque in Central Java which has various characteristics: Javanese,Persian and Arabian.Considering the model of the roof, the mosque exposesits Javanese characteristics; even its triple overlapping roof with the mustaka on the top reminds us to the Masjid Agung Demak. On the other hand, looking at its gate the mosque belongs to Persian and Arabian characteristics. The mosque which was founded by Kyai Adipati Surodimenggolo II is a series of historical development of the mosque in Semarang. In a short time, unfortunately, the mosque was on fire. In 23 April 1889 the mosque was rebuilt by G.I. Blume and Raden Tumenggung Cokrodipuro and by 23 November 1890 the rebuilding of the mosque completely finished. Suchinformation can be seen in the inscription on the sculpture at the mosque gate.